Development of STSE-based learning devices to improve the character of environmental care - Zuhair Abdullah (JURNAL BIOEDUKATIKA, 2020)
The character of environmental care is a serious problem in Indonesia, the low character of environmental care has an impact on environmental damage. One of the efforts to improve the character of environmental care for the community is through education, namely through the development of learning devices that can improve the character of environmental care. This study aims: 1) to produce a proper STSE-based device, 2) to produce a STSE-based device that is effective in enhancing the character of environmental care. This research is a development study using the Borg and Gall model. The developed device contains syllabus, lesson plans, handouts, and students worksheets. The product developed was tested on a limited trial to 12 grade X students and wider trials on 37 students using a pretest posttest control group design. The instruments used to assess the product are syllabus validation sheets, lesson plan validation sheets, handout validation sheets, and students worksheets validation sheets. The product was validated by 6 people, including two expert lecturers, two biology teachers, and two peers. The results showed: 1) the products produced were feasible in terms of content, graphics, and linguistics as evidenced by the average score of 4.2 in the very good category. 2) the resulting product is effective to improve the character of environmental care as evidenced by obtaining a score of 0.2 in the low category in the control class and 0.45 in the moderate category in the experimental class.